Análise energética de um sistema híbrido solar/gás para aquecimento de água em um edifício em João Pessoa - Silva Júnior, Olinto Evaristo da (2020)
The depletion of energy reserves of fossil origin has intensified interest in renewable energy sources, such as solar energy. Solar water heating represents an environmentally clean technology, with an abundant, permanent, renewable energy source, which does not pollute or harm the ecosystem. The use of this type of system, when installed in residential buildings, reflects a significant reduction in residential electrical consumption. In this context, the present dissertation was proposed to evaluate a hybrid heating system (solar / gas) for water in a residential building in the city of João Pessoa in two situations. Initially, in the configuration of the original project from available data (2012-2013) with recirculation of water from the plumb of the building and later in the current configuration via collected data (2018-2019) without recirculation of plumb water, with diversion to the cistern. The auxiliary system fuel in the original project, LPG (liquefied petroleum gas), was also replaced by natural gas (NG) in the current configuration. Therefore, an energy analysis was developed to verify the performance of the current system compared to the original system. The results obtained, via the F-Chart method, show that, as expected, the performance of the current system has decreased, causing a greater consumption of hot water and gas (due to the greater demand and lower calorific power of NG in relation to the GLP). For the development of the analyzes, a survey of system data (temperature and flow at characteristic points of the hybrid system) was carried out for the four years studied. It was found that, regardless of the configuration studied, the hybrid solar heating system (SAS), solar / gas, can replace the conventional system (electric showers), implying a reduction in consumption and electrical cost, by decreasing energy demand during peak hours and for the favorable effects on the environment, ensuring sustainability. However, in order for the advantages of SAS to be taken advantage of, the problems associated with its operational and control conditions must be minimized, so that the gas consumption of the auxiliary system is monitored to avoid energy losses and assess the energy cost of the system. hybrid installed. Evidencing that, only the hot water temperature control does not guarantee efficient operation with minimum energy losses.